Perancangan Permainan Digital Kisah Dewa Ruci sebagai Media Pengenalan Wayang bagi Remaja - Miki Tjandra; Irfansyah Irfansyah; Imam Santosa (Wimba : Jurnal Komunikasi Visual, 2012)
Teenagers today are more interested in modern western cultures and have gradually loosing respects for their own traditional cultures. Many of them have already started to forget the stories and arts of wayang. One form of modern culture that is increasingly favored by teenagers is digital game that presents diverse contents and ease of access as it can be played on a variety of electronic devices. This project is trying to reintroduce Indonesian wayang culture in the form of digital game to regain the interest of the teenagers. The story introduced in the game design is based on the legend of Dewa Ruci from the myths of wayang purwa. The story resolves around Bima and his journeys to find the water of life. The design method incorporates data collecting, data analysis and game design process. Fullerton's iteration method is applied in the process of game development. The methods used for data mining are based on the descriptive methods, implementing researches on the narratives and characters found in Dewa Ruci story both visually and philosophically, along with the substances of the story respectively. Data collections are derived from literatures and interviews. Information gathered such as Bima's heavy coarse features and his vicious Pancanaka, attributes such as Bima's poleng cloth and Candrakirana armlets, sacred mantras such as Jalasengsara and Bayu Braja, and Bima's adversaries confronted along the paths in finding the water of life are analyzed and developed into various visual assets in the game. The model of the game which is being developed is an action adventure side-scrolling platformer with a distinctive iconic character style, utilizing visual concepts derived from traditional shadow puppet's performance.